Pengaruh Kekuatan Otot Lengan Pada Hasil Servis Bawah Bola Voli Ekstrakurikuler SMP Negeri 3 Bangkinang Kabupaten Kampar - Nurjana, Mita (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2021)
The purpose of the study. The purpose of this study was to determine The Effect of Arm Muscle Strength on Lower Service Outcomes of Ektracurricular Students at SMP Negeri 3 Bangkinang, Kampar Regency. Materials and methods. The form of this research is a correlation study with the population of all extracurricular students of SMP Negeri 3 Bangkinang Kampar Regency with a total sample of 10 people. The sample in this study was obtained based on the total sampling technique used in this study, namely the arm muscle strength test and the lower service test result. Results. The results of data analysis in this study obtained r count of 0.987 with a large contribution of 97.41%. This is classified as very good. From the research conducted, it can be concluded that there is an influence of arm muscle strength on the ability of the underserving students of extracurricular students of SMP Negeri 3 Bangkinang, Kampar Regency. Where obtained r arithmetic 0.987>rtable = 0.632 with a contribution of 97.41%. Conclusions. Based on the data analysis that has been done, it can be concluded that this study has a the influence of arm muscle strength (X) on the bottom service result (Y) extracurricular students of SMPN 3 Bangkinang, Kampar Regency. Where r count 0.987>rtable 0.632, and there is a contribution of arm muscle strength to the results of lower serve volleyball for extracurricular students of SMPN 3 Bangkinang Kampar Regency of 97.41 % the remaining 2.583% is determined by other factors.